BRIDGING COGNITIVE ASSESSMENT AND EDUCATIONAL DIVERSITY: DESIGN AND APPLICATION OF A COGNITIVE AUTONOMY ASSESSMENT DEVICE - KUMARAN ARUL DEVARAM; Dr.S.GUNASEKARAN (The Bioscan, 2026)
The increasing diversity of learners in contemporary educational settings has created a need for assessment tools that can effectively measure cognitive autonomy across varied social, cultural, linguistic, and educational backgrounds. Cognitive autonomy, defined as an individual’s capacity for independent thinking, self-regulation, critical decision-making, and reflective learning, plays a crucial role in academic achievement and lifelong learning. This study presents the design, development, and application of a Cognitive Autonomy Assessment Device (CAAD) aimed at evaluating cognitive autonomy among diverse learner populations. The device was developed through a systematic process involving theoretical framework construction, item generation, expert validation, pilot testing, and psychometric evaluation. The assessment incorporates dimensions such as independent problem-solving, self-directed learning, critical thinking, decision-making confidence, and metacognitive awareness. Data were collected from students representing diverse educational, socio-economic, and cultural backgrounds to examine the reliability and validity of the instrument. Statistical analyses demonstrated strong internal consistency, construct validity, and measurement stability across different learner groups. Findings indicate that the CAAD effectively identifies variations in cognitive autonomy and provides valuable insights into learners’ independent learning capacities. The study highlights the potential of the device as an inclusive assessment tool that supports educational equity, personalized learning, and evidence-based instructional practices. The findings contribute to the growing discourse on diversity- sensitive educational assessment and offer practical implications for educators, researchers, and policymakers seeking to promote autonomous learning in increasingly heterogeneous educational environments.